EDITORIAL SCOPE : GEOTECHNICAL EARTHQUAKE ENGINEERING EDITION - Imtiyaz Akbar, Najar; Raudhah, Ahmadi (UNIMAS Publisher, 2023)
One of the main civil engineering disciplines is currently the focus area of the Journal of Civil Engineering, Science, and Technology (JCEST): geotechnical and earthquake engineering. We are honoured to present this editorial focusing on the dynamic and evolving field of geotechnical earthquake engineering, with an emphasis on seismic soil-structure interaction (SSI). These studies offer valuable insights into novel design methodologies, materials, and analysis approaches, which are crucial for ensuring the safety and resilience of infrastructure. This editorial paper collected information from the freely-accessible SCOPUS database to identify common keywords used in published papers pertaining to geotechnical earthquake engineering from 2015 to 2023. The analysis reveals that the ‘seismic’ and ‘structure’ terms are the most frequently utilised keyword in articles related to this field. As the editors of our esteemed journal, it is our privilege to shed light on this critical area of research that plays a pivotal role in ensuring the safety and resilience of civil infrastructure subjected to seismic forces.